Dexmedetomidine and propofol infusion on sedation characteristics in patients undergoing sciatic nerve block in combination with femoral nerve block via anterior approach - Yektaş,Abdulkadir (2015)
ABSTRACTOBJECTIVE: Dexmedetomidine is an a-2 adrenergic agonist having wide range of effects including sedation in mammalian brain, and has analgesic as well as sympatholytic properties. This study aimed to compare the effects of dexmedetomidine and propofol infusion on sedation characteristics in patients undergoing combined sciatic nerve and femoral nerve block via anterior approach for lower limb orthopedic procedure.METHODS: Forty patients, who were between 18 and 65 years old, this study was made at anesthesiology clinic of Bagcilar training and research hospital in 08 September 2011 to 07 June 2012, and underwent surgical procedure due to fractures lateral and medial malleol, were included. Sciatic nerve and femoral nerve block were conducted with an anterior approach on all patients included in the study, with an ultrasonography. The patients were randomly divided into dexmedetomidine [Group D (n = 20); 0.5 µg kg-1 h-1] and propofol [Group P (n = 20); 3 mg kg-1 h-1] infusion groups.RESULTS: The vital findings and intra-operative Ramsay sedation scale values were similar in both groups. Time taken for sedation to start and time required for sedation to become over of Group D were significantly higher than those of Group P (p < 0.001 for each).CONCLUSIONS: Substitution of dexmedetomidine instead of propofol prolongs the times to start of sedation, the times to end of sedation and duration of sedation.